Investigating microplastic dynamics in soils: Orientation for sampling strategies and sample pre‐procession. (20th August 2020) - Weber, Collin Joel; Weihrauch, Christoph; Opp, Christian; Chifflard, Peter
Abstract: Studies on microplastics in soils is currently being established as a new research field. So far, mainly 'explorative studies' have been carried out to detect microplastics in different soil environments. To generate a deeper understanding of microplastics dynamics, 'systematic studies' are required. Such research must built on a targeted sampling strategy and considerate fieldwork and sample handling. From literature enquiry, a five‐stage methodological workflow was deduced for studies on microplastics in soils. In the present review, the spatial representation of soils/soilscapes with microplastics in soils research is conceptually and practically assessed. We discuss judgmental, randomized, and metric soil sampling strategies. Then, we explain sample pre‐processing and give a brief overview of methods for microplastics identification and quantification. We conclude that the establishment of the novel field of research 'microplastic dynamics in soils' requires more intensive consideration of soil sampling strategies. As soil is a complex medium and the soilscape is spatially heterogeneous, we highlight systematic sampling strategies as the best possible options for sophisticated research. However, no overall optimum methodology can be defined because the specific strategy must be in line with the particular research question. For all studies on microplastics in soils, practical improvement is needed to prevent contamination of soil samples with plastics during sampling and sample pre‐processing.